The effects of lactic acid bacteria inoculants and formic acid on the formation of biogenic amines in grass silages - Steidlová, S; Kalac, P (Archives of animal nutrition, 2004)
Silages were prepared in six laboratory experiments from four direct-cut grassland swards and pure swards of perennial ryegrass and false oat with dry matter contents ranging between 180 and 325 g/kg. Grass was fermented at 22 degrees C and silages were stored at the same temperature for 4 months. Untreated silages (negative control) and silages preserved with 3 g/kg of formic acid (positive control) were compared with silages inoculated with commercial strains of Lactobacillus plantarum, Lactobacillus buchneri and a mixed preparation Microsil. The inoculants were applied at a dose of 5.10(6) CFU/g of grass. Seven biogenic amines were extracted from silages with perchloric acid and determined as N-benzamides by micellar electrokinetic capillary chromatography. Common chemical quality parameters of silages were also determined. Tyramine, cadaverine and putrescine were the amines occurring at the highest concentration. As compared to untreated silages, formic acid was most effective to suppress formation of the main amines. Also the inoculants often decreased amine contents significantly (P < 0.05). The inoculants decreased levels of polyamine spermidine more efficiently than formic acid. Contents of histamine, tryptamine and polyamine spermine were very low, commonly below the detection limits.
Keywords: Biogenic Amines; Animals; Food Microbiology; formiáty; Formates; Lactobacillus; počet mikrobiálních kolonií; Food Handling; fermentace; Colony Count, Microbial; Poaceae; potravinářská mikrobiologie; manipulace s potravinami; Chromatography; siláž; lipnicovité; Fermentation; zvířata; Silage; chromatografie; biogenní aminy